THE USE OF CLUSTERING TECHNIQUE TO IMPROVE THE STUDENTSâ SKILL IN WRITING DESCRIPTIVE PARAGRAPH - Sari, Farnia; Wahyuni, Sri (English Community Journal, 2018)
Writing process involves thinking and creative skills. To stimulate the studentsâ thoughts to express their ideas, clustering technique is effective brainstorming activity to help the students explore their ideas and write consistently. Thus, the objective of this study is to find out whether or not there is any significant difference between the students who were taught in writing descriptive paragraph through Clustering Technique and those who were not. The population of this study was all of the eighth grade students of SMP Srijaya Negara Palembang in academic year 2016/2017. There were three classes that consist of 113 students. The samples of this study were VIII C as a control group and VIII B as an experimental group. This study was conducted by using quasi experimental method with nonequivalent control group design. Then, the data were analyzed by using paired sample t-test and independent sample t-test. The result of independent sample t-test shows that the value of sig. (2-tailed) was 0.00 < 0.05 in the level of significant 0.05. While, the value of t-obtained was 5.213 higher than the critical value of t-table was 1.665 with degree of freedom 76. It can be concluded that the null hypothesis was rejected and the alternative hypothesis was accepted. It means that there was any significant difference between the students who were taught in writing descriptive paragraph through Clustering Technique and those who were not.